A non-enzymatic electrochemical biosensor based on Au@PBA(Ni–Fe):MoS2 nanocubes for stable and sensitive detection of hydrogen peroxide released from living cells. Issue 48 (22nd November 2019) - Zhang, Wang; Wang, Chao; Guan, Lihao; Peng, Meihong; Li, Kai; Lin, Yuqing
Abstract : Hydrogen peroxide (H2 O2 ) is the main product of enzymatic reactions and plays an important role in biological processes. Abstract : Hydrogen peroxide (H2 O2 ) is the main product of enzymatic reactions and plays an important role in biological processes. The detection of H2 O2 inside organisms or cells is critical. Here, we report a nickel–iron Prussian blue analogue nanocube doped with molybdenum disulfide and Au nanoparticles (Au@PBA(Ni–Fe):MoS2 ) as an electrochemical sensing material for the stable detection of H2 O2 in neutral solutions for a long time. First, the Prussian blue analogue (PBA(Ni–Fe)) is synthesized by a simple charge-assembly technology, and then etched into PBA(Ni–Fe):MoS2 hollow nanocubes by a high-temperature hydrothermal reaction. Finally, Au nanoparticles are reduced inside the PBA(Ni–Fe):MoS2 in situ to generate Au@PBA(Ni–Fe):MoS2 nanocubes. Ni-doping enhances the nanocube's stability in neutral solutions; as a result, the sensor can maintain a stable current response towards H2 O2 reduction for more than 1 h. The sensing material can meet the needs of a long-time test. The introduction of Au enhances the electron transfer efficiency, which endows the sensor with good reduction ability for H2 O2 at 0 V over a wide linear range (0.5–200 μM and 210–3000 μM) and with a low detection limit (0.23 μM (S/N = 3)), which fulfills the requirements for the detection of H2 O2 in a biological system. The sensor can sense H2 O2 released from cells stimulated by ascorbic acid. Au@PBA(Ni–Fe):MoS2 provides good guidance for the future development of efficient biosensors to be applied in cell biology.